Can Angle's type II malocclusion be treated with the exclusive use of a Bull-type retraction loop? Clinical case report (Research, Society and Development, 2021)
Angle Class II malocclusion is characterized by an anteroposterior dental discrepancy, which is usually accompanied by skeletal changes. The late orthodontic treatment allows the correction of this malocclusion with the need for tooth extractions. This report presents an Angle class II treatment option with the use of a retraction loop of the Bull type, addressing the advantages of the technique and establishing its effectiveness. Male patient, with a convex facial profile was diagnosed with Angle class II. The treatment started with conventional orthodontic brackets, and placement of a modified anterior lift plate with transpalatal bar. Subsequently, extraction of the first maxillary premolars was performed and the anterior segment was retracted using the Bull Loop retraction loop until the spaces were closed, and canine angulation in class I was achieve, in addition to good occlusal stabilization. Finally, a 3x3 fixed retainer and superior removable braces were installed to preserve the achieved dental positions. The patient presented satisfactory results, with all guides and functions restored, in addition to a harmonic profile, thus showing the effectiveness of the approached technique.